Decellularized blood vessel development: Current state-of-the-art and future directions - Wang, Xinyu; Chan, Vincent; Corridon, Peter R. (Frontiers in Bioengineering and Biotechnology, 2022)
Vascular diseases contribute to intensive and irreversible damage, and current treatments include medications, rehabilitation, and surgical interventions. Often, these diseases require some form of vascular replacement therapy (VRT) to help patients overcome life-threatening conditions and traumatic injuries annually. Current VRTs rely on harvesting blood vessels from various regions of the body like the arms, legs, chest, and abdomen. However, these procedures also produce further complications like donor site morbidity. Such common comorbidities may lead to substantial pain, infections, decreased function, and additional reconstructive or cosmetic surgeries. Vascular tissue engineering technology promises to reduce or eliminate these issues, and the existing state of the art approach is based on synthetic or natural polymer tubes aiming to mimic various types of blood vessel. Burgeoning decellularization techniques are considered as the most viable tissue engineering strategy to fill these gaps. This review discusses various approaches and the mechanisms behind decellularization techniques and outlines a simplified model for a replacement vascular unit. The current state of the art method used to create decellularized vessel segments is identified. Also, perspectives on future directions to engineer small- (inner diameter > 1 mm and < 6 mm) to large-caliber (inner diameter > 6 mm) vessel substitutes are presented.